The London handicap scale: a re-evaluation of its validity using standard scoring and simple summation. Issue 3 (1st March 2000) - Jenkinson, Crispin; Mant, Jonathan; Carter, Judy; Wade, Derick; Winner, Simon
Abstract : OBJECTIVE: To assess the validity of the London handicap scale (LHS) using a simple unweighted scoring system compared with traditional weighted scoring METHODS: 323 patients admitted to hospital with acute stroke were followed up by interview 6 months after their stroke as part of a trial looking at the impact of a family support organiser. Outcome measures included the six item LHS, the Dartmouth COOP charts, the Frenchay activities index, the Barthel index, and the hospital anxiety and depression scale. Patients' handicap score was calculated both using the standard procedure (with weighting) for the LHS, and using a simple summation procedure without weighting (U-LHS). Construct validity of both LHS and U-LHS was assessed by testing their correlations with the other outcome measures. RESULTS: Cronbach's α for the LHS was 0.83. The U-LHS was highly correlated with the LHS ( r =0.98). Correlation of U-LHS with the other outcome measures gave very similar results to correlation of LHS with these measures. CONCLUSION: Simple summation scoring of the LHS does not lead to any change in the measurement properties of the instrument compared with standard weighted scoring. Unweighted scores are easier to calculate and interpret, so it is recommended that these are used.